Examination of incident reports performed by orthoptists at Ohshima Hospital of Ophthalmology - Haruno, Yoshiko; Magome, Kazuyoshi; Nagai, Hirofumi; Yamada, Toshio; Matsui, Takaaki (JAPANESE ORTHOPTIC JOURNAL, 2007)
Purpose: To analyze the incident reports issued by orthoptists at Ohshima Hospital of Ophthalmology. Subjects and Methods: The analysis included incident reports from 13 orthoptists. The incident reports submitted to Ohshima Eye Examination Department from Jan 2005 to Mar 2006 were analyzed. Results: The total number of incident reports was 192 cases. Eighty nine cases are involved in ophthalmic examinations, 22 cases in handling of patient records, and 20 cases in accidental falling down, respectively. Ophtalmic examination affairs were classified into the following three categories, 26 cases during eyesight test, 23 cases during ophthalmic ultrasonography, and 9 cases during refraction/intraocular pressure/visual field tests, respectively. The causes of the incidences derived from distraction and misunderstanding in 64 cases, lack of reconfirmation sought in 55 cases, environmental or system probrem in 21 cases, and poor knowledge or technique in 16 cases, respectively. Conclusion: The majority of incidents reported here appeared to be caused by orthoptist. To prevent these incidents, we should not only improve our skill, knowledge, and powers of concentration, but also innovate a plan for safety.